2018
DOI: 10.1111/nyas.13969
|View full text |Cite
|
Sign up to set email alerts
|

The gut–brain axis in health neuroscience: implications for functional gastrointestinal disorders and appetite regulation

Abstract: Over the past few years, scientific interest in the gut-brain axis (i.e., the bidirectional communication system between the gastrointestinal tract and the brain) has exploded, mostly due to the identification of the gut microbiota as a novel key player in this communication. However, important progress has also been made in other aspects of gut-brain axis research, which has been relatively underemphasized in the review literature. Therefore, in this review, we provide a comprehensive, although not exhaustive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 148 publications
(398 reference statements)
0
30
0
2
Order By: Relevance
“…Cortisol in turn affects various immune cells (including cytokine secretion) locally in the gut, subsequently inducing changes to microbiota composition, and increasing the gastrointestinal permeability (de Punder and Pruimboom, 2015;Kelly et al, 2015;Farzi et al, 2018). Hence, an exceedingly complex array of signaling systems, all interlinked, lies between the brain and gut in the "top-down" concept (Aziz and Thompson, 1998;Collins and Bercik, 2009;O'Mahony et al, 2009;Forsythe et al, 2014;Khlevner et al, 2018;Weltens et al, 2018;Zhao et al, 2018). The CNS is well shielded by the BBB, the major site of blood-CNS exchange.…”
Section: Main Findings Referencesmentioning
confidence: 99%
“…Cortisol in turn affects various immune cells (including cytokine secretion) locally in the gut, subsequently inducing changes to microbiota composition, and increasing the gastrointestinal permeability (de Punder and Pruimboom, 2015;Kelly et al, 2015;Farzi et al, 2018). Hence, an exceedingly complex array of signaling systems, all interlinked, lies between the brain and gut in the "top-down" concept (Aziz and Thompson, 1998;Collins and Bercik, 2009;O'Mahony et al, 2009;Forsythe et al, 2014;Khlevner et al, 2018;Weltens et al, 2018;Zhao et al, 2018). The CNS is well shielded by the BBB, the major site of blood-CNS exchange.…”
Section: Main Findings Referencesmentioning
confidence: 99%
“…94 There are well-known neural connections between gut and brain, and those organisms may affect psychiatric disorders, including EDs. 95 Various studies in participants with AN have found alterations compared with controls in microbial composition, and microbe diversity in AN may correlate with body mass index and also, for instance, blood insulin levels. [96][97][98] Healthy competitive athletes had the highest number of microbiota species compared with ED and control groups, significantly higher versus both AN and obese individuals.…”
Section: Microbiota and Microbiomementioning
confidence: 99%
“…Eating behaviour in association with weight status represents a research field of great interest and current data revealed that appetitive traits are genetically predisposed and differ significantly between normal weight and obese subjects [ 33 , 34 ]. Recent studies have shown that hormones regulating food intake are differentially expressed in obese and normal-weight people [ 35 ], while childhood obesity has been considered as a risk factor for the later development of disordered eating behaviours [ 36 ]. In terms of appetite and hunger no differences have been observed within the groups when asked about their eating habits.…”
Section: Discussionmentioning
confidence: 99%